Feeding ecology and abundance of Lesser Whistling Duck (Dendrocygna javanica Horsfield) in Paya Indah Wetlands, Malaysia - Chukwuemeka, Onwuka Martins (2017)
To ascertain the food types, abundance and habitat selection of Lesser Whistling Duck (Dendrocygna javanica) is highly crucial for conservation and future management activities. There is little or no study on the food type selection and population of D. javanica. In this study, habitat selection of D. javanica in 14 heterogeneous lakes (direct visual observation & point sampling technique) and feeding ecology (scan through method) were investigated from April-September, 2016. Other ecological parameters such as water temperature, pH, Water Quality Index (WQI), Water Level Fluctuation (WLF), lake size were also taken. It was observed that Belibis Lake was heavily preferred by D. javanica (i.e., 166.16 ducks individuals). However, three lakes i.e., Seroja, Telipok and Drift Wood were completely avoided by D. javanica (i.e., no individual was observed) during the study period. The highest pH value was observed in Grebe Lake (September 2016; pH-8.9) and the lowest one in Seroja Lake (May 2016; pH-6.3). Likewise, the highest mean water temperature was recorded in Senduduk Lake (June 2016; 32.9°C) and the lowest one was determined in Grebe Lake (July 2016; 20.7 °C). Multivariate analysis i.e., correlation matrix identified multicollinearity relationship between relative abundance of Lesser Whistling Duck with Water Level Fluctuation (WLF),Water Quality Index (WQI), Lake Size (LS) and Normalized Dorminant Vegetation Index (NDVI). Inter-specific variation analysis showed that habitat selection by D. javanica occurs at a species-specific level in responses to changes in environmental factors. D. javanica preferred Belibis lake (Mean abundance = 27 individuals/month, lake size =50939.5m2, water depth = 3.38m, slope ± SE = -0.004 ± 0.309; P<0.001).Therefore, this study showed that the quality of the lakes, vegetation type and food richness/availability (i.e aquatic plants and invertebrates) were responsible for D. javanica abundance in Belibis lake compared to every other lake. In conclusion, this study indicates that in order for the population to strive well, the wetland habitats especially water depth and food type richness should be the priority in managing D. javanica.